2015
DOI: 10.1615/critrevimmunol.2015012295
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of Cholera Toxin in the Modulation of TH17 Responses

Abstract: Numerous studies have shown that TH17 cells and their signature cytokine IL-17A are critical to host defense against various bacterial and fungal infections. The protective responses mediated by TH17 cells and IL-17A include the recruitment of neutrophils, release of antimicrobial peptides and chemokines, and enhanced tight junction of epithelial cells. Due to the importance of TH17 cells in infections, efforts have been made to develop TH17-based vaccines. The goal of vaccination is to establish a protective … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 165 publications
(152 reference statements)
1
6
0
Order By: Relevance
“…In contrast, we showed that CXCL10 was less effective than CT as an adjuvant in the intrarectal pull step. A major mechanism behind CT's adjuvant activity is stimulating antigen-presenting cells for enhanced antigen presentation (24,41,42). This property of CT is consistent with our notion that the rectum homing of primed CD8+ T cells is mainly licensed by ligation to locally presented cognate antigens.…”
Section: Discussionsupporting
confidence: 88%
“…In contrast, we showed that CXCL10 was less effective than CT as an adjuvant in the intrarectal pull step. A major mechanism behind CT's adjuvant activity is stimulating antigen-presenting cells for enhanced antigen presentation (24,41,42). This property of CT is consistent with our notion that the rectum homing of primed CD8+ T cells is mainly licensed by ligation to locally presented cognate antigens.…”
Section: Discussionsupporting
confidence: 88%
“…administration. The cytokine IL‐17 has been implicated in regulation of inflammation and autoimmune diseases . It is notable that our recent data shows that mice immunized with ovalbumin in the absence of CT adjuvant produce lower antibody titers than those immunized in the presence of CT adjuvant (data not shown).…”
Section: Discussionmentioning
confidence: 81%
“…immunization requires mixing of CT with the vaccine to trigger an appropriate immune response. The mucosal adjuvant activity of CT involves induction of IL‐1 and other proinflammatory cytokines . Thus, we suspect that CT may nonspecifically trigger the induction of IL‐17; however, administration of CT alone did not induce IL‐17.…”
Section: Discussionmentioning
confidence: 98%
“…There has been significant interest in using CT and LT as adjuvants in vaccination, and understanding how it is able to steer T cell responses provides insight in how to better improve vaccination or to engineer nontoxic derivatives that are able to promote its adjuvancy (72)(73)(74)(75).…”
Section: Elimination Of T Cellsmentioning
confidence: 99%